Antidiabetic, angiotensin‐converting enzyme inhibitory and anti‐inflammatory activities of fermented camel milk and characterisation of novel bioactive peptides from lactic‐fermented camel milk with molecular interaction study. (10th November 2022) - Shukla, Pratik; Sakure, Amar; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Das, Sujit; Liu, Zhenbin; Padhi, Srichandan; Rai, Amit Kumar; Hati, Subrota
Abstract : This study was to separate and purify antidiabetic and angiotensin‐converting enzyme (ACE) inhibitory peptides from Lactiplantibacillus plantarum KGL3A fermented camel milk. After 48 h of fermentation at 37°C, ɑ‐amylase inhibition, ɑ‐glucosidase inhibition, lipase inhibition and ACE inhibitory activities were 80.94%, 64.45%, 63.93%, and 77.53%, respectively in fermented camel milk. Optimisation of growth condition for the evaluation of maximum peptide production was evaluated by measuring proteolytic activity ( O ‐phthalaldehyde, OPA method) with different inoculation rates and incubation times and highest proteolytic activity (9.21 mg/mL) was observed after 48 h of fermentation at 2.5% rate of inoculation. The antidiabetic and ACE inhibitory activity of 3 kDa permeate fraction were higher as compared with other fractions. Purification of antidiabetic and ACE inhibitory peptides from fermented camel milks was performed through sodium dodecyl‐sulphate polyacrylamide gel electrophoresis, and 2‐dimensional polyacrylamide gel electrophoresis and maximum number of protein bands were present in between 25 and 10 kDa. The generated peptide sequences were matched with antihypertensive peptide database (AHTPDB) and BIOPEP databases for confirming the antidiabetic and ACE inhibitory activity. Peptides, that is. TDVMPQWW and MMSLVSLLLVGILFPTIQAK were having highest peptide ranker score among the all sequences. Furthermore, anti‐inflammatory activity (TNF‐α, IL‐6 and IL‐1β) of fermented camel milk was evaluated in macrophage cell line RAW 264.7 (Ralph and William's cell line). Furthermore, peptides were predicted to have improved binding affinity against Human Angiotensin converting enzyme (hACE) through molecular docking. Abstract : Biofunctional properties and antidiabaetic peptides from fermented camel milk.